Energetics of Co-ordinately Controlled Two-coordinate Positioning System - Gelezevičius, V. (Elektronika ir Elektrotechnika, 1997)
Energetical efficiency of coordinately controlled two-coordinate positioning system is investigated in this article. The power losses of coordinately controlled two-coordinate positioning system are compared with the power losses of the same system in the case, when both drives of them act independently. The limits of area in which the method of co-ordinate control is energetically efficient are established.